Evaluation of Some Roughages for Ruminant Nutrition - Filik, AG; Ertürk, MM (Journal of the Hellenic Veterinary Medical Society, 2023)
The present study was conducted to determine the feed quality of the plants cultivated for the production of roughage plants at 186 different locations in the Western Mediterranean region, Türkiye. The main material of the study, 11 different roughage sources (Legume and Wheatgrass Forages) or their mixtures were collected from the center and 24 districts of three provinces (Antalya (8), Isparta (10) and Burdur (9)) representing the region. Legumes; alfalfa hay (37), vetch stalk (8), Wheatgrass; barley stalk (28), wheat fodder (2), wheat stalk (49), oat stalk (12), grass hay (18), and mixtures; Barley-oat stalk (11), barley-wheat stalk (5), barley-vetch stalk (13) and vetch-oat stalk (3) mixtures of roughages were the main materials of the study that were determined nutrient contents, feed and energy values. The relative feed value (RFV) and the relative feed quality (RFQ) results of all roughages; vetch stalk 102.42±11.01 & 113.69±13.22, alfalfa hay 99.17±3.03 & 112.41±3.42 for legumes; among the wheats; grass hay 99.50±9.54 & 113.05±11.01, oat stalk 80.84±3.22 & 84.27±2.89, wheat fodder 78.69±1.59 & 83.83±1.59, barley stalk 67.72±3.46 & 69.45±2.56, wheat stalk 48.88±1.97 & 56.97±1.44 and mixed roughages were determined as vetch-oat stalk 100.49±7.12 & 108.18±7.53, barley-vetch stalk 92.58±5.32 & 97.14±5.37, barley-oat stalk 93.21±5.61 & 92.93±4.75 and barley-wheat stalk 81.97±10.73 & 81.36±9.34. Grass hay, vetch stalk and vetch-oat stalk were determined as a third quality roughage according to the RFV. According to RFQ; grass hay, vetch stalk and alfalfa hay are used in feeding heifer, 12 to 18 months beef cow-calf, while vetch-oat stalk is in the class of roughage to be used in feeding heifer are described as 18 to 24 months dry cow. As a result, due to the wrong harvesting time and harvests made with inappropriate equipment, serious nutrient losses occur in roughages until they reach the animal’s feed.